Sounion Revisited: The Sanctuaries of Poseidon and Athena at Sounion in Attica - Zetta Theodoropoulou Polychroniadis (Les Carnets de l’ACoSt)
This book is the first to be published from a wider research project, still in progress, about the sanctuaries of Poseidon and Athena on the promontory of Sounion.